Blood-pressure variability is buffered by nitric oxide - Nafz, Benno; Just, Armin; Stauβ, Harald M.; Wagner, Claus D.; Ehmke, Heimo; Kirchheim, Hartmut; Persson, Pontus B. (Journal of the autonomic nervous system, 1996)
The baroreflex constitutes the only hitherto known buffer of rapid blood pressure oscillations. In order to investigate the influence of nitric oxide (NO) and the sinoaortic and cardiopulmonary baroreflex pathways on the dynamic properties of blood pressure control, we determined the power spectra of 24-h blood pressure time series of conscious dogs. This was done in the intact state (n = 6), during blockade of NO synthesis via the false substrate NG-nitro-l-arginine ((l-NNA), 16.5 ± 2 mg/kg body weight i.v., n = 5) and in animals devoid of baroreceptor reflexes (n = 5). After l-NNA, blood pressure (BP) increased by roughly 20 mmHg to 137 ± 6 mmHg (P < 0.01), heart rate decreased from 97 ± 6 to 68 ± 3 beats/min (P < 0.01). The power of blood pressure variations within the frequency range 0.1-0.5 Hz was tripled by l-NNA (P < 0.05). By comparison total sinoaortic and cardiopulmonary denervation increased power of slower oscillations (< 0.1 Hz) by a factor of 4.7 (P < 0.05). Thus, NO and the baroreceptor reflex both play an important role as physiological blood pressure buffers, NO for rapid (0.1-0.5 Hz) and the baroreflex for slower fluctuations (< 0.1 Hz).
Elektronische Reproduktion der Druck-Ausgabe 2. März 1996
Gesehen am 21.11.2024